Critical Dynamics of Lemito Village Apparatus' Behavior in Public Services in Pohuwato Regency - Djafar, Franky; Tilome, Apris Ara; Sialo, Yunita (Journal of Public Representative and Society Provision, 2023)
This research aims to analyze the dynamics of the behavior of officials in Lemito Village in public services in Pohuwato Regency, with a focus on four key indicators: Responding to Service Recipients, Maintaining Effective Communication, Taking Responsibility, and Acting for Customers. Using a qualitative approach, data were collected through in-depth interviews, participatory observation, and documentary studies. Theories of public management, community participation, organizational communication, and total quality management were integrated to form the conceptual framework of the research. The research findings indicate that the behavior of officials in Lemito Village still has weaknesses in responding quickly to the needs of the community, maintaining effective communication, taking active responsibility, and acting proactively to meet customer expectations. These findings reflect suboptimal public services influenced by several factors, including a lack of training, communication barriers, and a lack of community participation in decision-making. The conclusion of the research emphasizes that improvements in the behavior of officials in Lemito Village will contribute to the enhancement of the quality of public services, creating better relationships between village officials and the community, and promoting the achievement of development goals at the local level. Recommendations include the need for regular training to improve the responsiveness and effectiveness of village officials, the development of intercultural communication skills, local empowerment through community participation in decision-making processes, and the introduction of a reward system to encourage responsibility and proactive initiatives.